Meal Replacements for Weight-Related Complications in Type 2 Diabetes: What Is the State of the Evidence? - Noronha, Jarvis C.; Kendall, Cyril WC.; Sievenpiper, John L. (Frontiers in Endocrinology, 2022)
Comprehensive lifestyle management is a fundamental aspect of diabetes care. Clinical practice guidelines for the nutritional management of diabetes have evolved considerably over the last 25 years shifting from a focus on single nutrients to food- and dietary pattern-based recommendations. Use of meal replacements as a temporary short-term strategy to induce weight loss and then transitioning to a healthier dietary pattern (e.g., Mediterranean or Portfolio) for weight loss maintenance fits well with this new shift in focus of clinical practice guidelines. As adherence is the most important determinant for attaining the benefits of any diet, health professionals should recommend evidence-based dietary patterns (including meal replacements) that align best with the patient’s values, preferences, and treatment goals.